Complete enucleation surgical treatment and histological analysis of a mucocele in lower lip in a child: Case Report. - Mariana Braga de Vasconcelos; Daniela Novaes Soares; Thais Campos Rodrigues Soares; Gabriela Andrade Americano; Roberto de Almeida Elias; Tatiana da Silva Fidalgo (Universidad de Concepción., 2019)
Objective: The aim of this case report is to describe the surgical removal of a mucocele and its histological analysis, in a child. Case Report: An 11-year-old female patient attended the Pediatric Dentistry clinic complaining of a lower lip lesion. During the anamnesis, the mother reported that the child had a habit of biting and sucking the spot frequently. Clinical examination showed the lesion was compatible with a mucocele. The proposed treatment was a complete enucleation of the lesion under local anesthesia. The incision and tissue divulsion were performed for maximum preservation of the mucosa, avoiding a possible recurrence. Total adjacent glands removal was also performed. The lesion was placed in 10% formaldehyde for histopathological analysis (H&E Staining), which showed dense connective tissue presenting chronic inflammatory infiltrate and extravasated mucin, presence of granulation tissue delimiting the area of extravasated mucin and presence of minor salivary glands. The patient was advised to quit the habit, and after seven days the sutures were removed. At the one-year follow-up there was no recurrence of the lesion. Conclusion: The proposed treatment proved to be effective without recurrence of the lesion.